2018
DOI: 10.1002/adma.201805082
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Doping Enables a Two‐Dimensional Electron Gas for High‐Performance Homojunction Oxide Thin‐Film Transistors

Abstract: deposition (PLD), and radiofrequency sputtering. [2,[11][12][13] Nevertheless, solutionprocessing of MO precursors holds significant promise for lower cost production and compatibility with flexible substrates. [2,9,14,15] In this regard, indium oxide (In 2 O 3 ) is one of the most investigated solution-processed oxide semiconductors, [7,[16][17][18][19][20][21] however, the carrier density of pristine In 2 O 3 is difficult to control and In 2 O 3 films are usually polycrystalline, limiting their performance u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 53 publications
1
43
0
Order By: Relevance
“…The markedly improved electrical performance originated from the presence of free electrons confined on the heterointerface plane, which were induced by the large conduction band offset between ZnO and In 2 O 3 . The 2DEG was further realized via polymer‐doped oxide TFTs by fabricating a homojunction of In 2 O 3 and polyethylenimine (PEI)‐doped In 2 O 3 . The resultant TFTs achieved decent μ FE of 10 cm 2 V −1 s −1 on a 300 nm SiO 2 gate dielectric.…”
Section: Metal Oxide Tftsmentioning
confidence: 99%
“…The markedly improved electrical performance originated from the presence of free electrons confined on the heterointerface plane, which were induced by the large conduction band offset between ZnO and In 2 O 3 . The 2DEG was further realized via polymer‐doped oxide TFTs by fabricating a homojunction of In 2 O 3 and polyethylenimine (PEI)‐doped In 2 O 3 . The resultant TFTs achieved decent μ FE of 10 cm 2 V −1 s −1 on a 300 nm SiO 2 gate dielectric.…”
Section: Metal Oxide Tftsmentioning
confidence: 99%
“…By adjusting the thickness of AlInO and the doping amount of Al, AlInO (30%)/In 2 O 3 heterostructure TFTs with a high mobility of 40 cm 2 /Vs, a threshold slope of 0.7 V/dec, and an on/off ratio of 10 7 could be realized [58]. [56]. The 2D electron gas was achieved by creating a band offset between In2O3 and In2O3:PEI via work function tuning of the PEI-doping ratio.…”
Section: Mobility Enhancement By Forming 2d Electron Gasmentioning
confidence: 99%
“…When the doping amount of Li was 20%, the mobility of In 2 O 3 /Li-ZnO heterojunction TFTs reached the maximum value of 11.4 cm 2 /Vs and the on/off current ratio of ~10 5 . Chen et al demonstrated high performance In 2 O 3 /In 2 O 3 :polyethylenimine (PEI) heterostructure TFTs [ 56 ]. The 2D electron gas was achieved by creating a band offset between In 2 O 3 and In 2 O 3 :PEI via work function tuning of the PEI-doping ratio.…”
Section: Heterojunction Oxide Tftsmentioning
confidence: 99%
“…Similarly, the mobility enhancement in n‐type oxide TFTs by n‐doping was recently reported. [ 14 ] It is worthy to note that the F 4 TCNQ layers delivered insulating behavior with low conduction current of several tens of picoamperes (Figure S3, Supporting Information). This confirms that the performance enhancement of F 4 TCNQ‐inserted Cu x O TFTs originated from charge transfer p‐type doping rather than from the conductance of F 4 TCNQ layers.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike conventional atomic substitution doping, the doping process does not induce any defects or impurities into the host lattice, thereby eliminating undesired carrier scattering while reserving the fundamental transport properties. [ 11 ] Originally, MCTD was mainly used with organic semiconductors [ 12,13 ] and recently has been extended to n‐type metal oxides [ 14,15 ] and low‐dimensional nanomaterials (2D semiconductors, [ 16 ] carbon nanotubes, [ 17,18 ] and nanocrystals [ 19 ] ). For p‐type MCTD doping, the dopants should have a higher electron affinity than that of the host materials; commonly used candidates are MoO 3 , NO 2 , and tetrafluoro‐tetracyanoquinodimethane (F 4 TCNQ).…”
Section: Introductionmentioning
confidence: 99%